Variabilidade genética e análise de parentesco de animais de cativeiro Muriqui-do-sul (Brachyteles arachnoides, E. GEOFFROY, 1806) - Magrini, Fernando Peron (2016)
The main threat to biodiversity and genetic diversity of natural populations is habitat fragmentation, caused by continuous anthropic actions such as deforestation, mining and hunting, all connected to human development. These activities have direct consequences on both vegetal and animal species, altering richness and modifying population dynamics by affecting physical, chemical and biological processes linked to the populations. In this context, captive populations of threatened animals take on huge responsibility onto conservation of several species providing a source of genetic material and ecological relations. Therefore, management of these populations is fundamental to avoid captive associated problems, and one of many tools used to achieve such goals resides in the genetic characterization of populations. The southern muriqui is the biggest neotropical primate, endemic of Atlantic Forest, it is in the threatened animals list of IUCN at the category “Endangered”. We used 8 heterologous microssatellite loci to characterize the genetic variability and verify possible parentage relationships between 18 captive individuals. Results show that the allelic richness and genetic diversity identified in captive animals is similar, otherwise higher when compared to other captive and in situ studies, contradicting prevailing literature. We achieved values of mean expected heterozygosity of 0,619 and mean richness of 5,253. Parentage analysis may have left some doubts still, but revealed several new relationships between some individuals whose pre-captive origin is uncertain. This essay supplies fundamental information for creating an ex situ management strategy aiming reproduction and maintaining genetic variation found at Brazil´s captivities today. We also stress the importance and need to produce a studbook for this specie, which may assist the management itself as well as future work with the specie.